Can venous-to-arterial carbon dioxide differences reflect microcirculatory alterations in patients with septic shock? (2016)
Purpose Septic shock has been associated with microvascular alterations and these in turn with the development of organ dysfunction. Despite advances in video microscopic techniques, evaluation of microcirculation at the bedside is still limited. Venous-to-arterial carbon dioxide difference (Pv-aCO2) may be increased even when venous O2 saturation (SvO2) and cardiac output look normal, which could suggests microvascular derangements. We sought to evaluate whether Pv-aCO2 can reflect the adequacy of microvascular perfusion during the early stages of resuscitation of septic shock.